(untitled) (Shaheed Smriti Journal, 2025)
Pearl S. Buck’s The Good Earth (1931) offers a powerful depiction of rural life in early twentieth-century China, foregrounding the intimate relationship between human survival and the land. Despite the novel’s critical acclaim, its thematic complexity, particularly the intersections of land ownership, social hierarchy, gender relations, and personal identity, has not always been examined through an integrated analytical framework. This study addresses this gap by investigating how Buck uses the life of Wang Lung to reflect broader social and moral transformations within a traditional agrarian society. Employing a qualitative textual analysis, the research draws on close reading and socio-cultural interpretation to examine key narrative episodes, character development, and symbolic representations of land and wealth. The findings reveal that the land functions not only as a source of material prosperity but also as a moral anchor that shapes identity and social order. As Wang Lung rises and falls economically, the novel illustrates a recurring cycle of moral integrity followed by corruption, highlighting the tension between tradition and change. The study concludes that The Good Earth ultimately presents agrarian life as both sustaining and restrictive, suggesting that human fulfillment is deeply tied to ethical balance rather than material accumulation alone.